2021
DOI: 10.1101/2021.11.24.21266837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in antidepressant use in Australia: A nationwide analysis prior to and during the COVID-19 pandemic (2015-2021)

Abstract: BackgroundDepression and anxiety affect 4% to 14% of Australians every year; symptoms may have been exacerbated during the COVID-19 pandemic. We examined recent patterns of antidepressant use in Australia in the period 2015 to 2021, which includes the first year of the pandemic.MethodsWe used national dispensing claims for people aged ≥10 years to investigate annual trends in prevalent and new antidepressant use (no antidepressants dispensed in the year prior). We conducted stratified analyses by sex, age grou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous studies already investigated the impact of lockdown on antidepressant drug (AD) use. In particular, some studies reported an increased use of these medications during the first wave [15,16] that in some case persist also during the subsequent period of 2020 [17][18][19][20]. On the contrary, other studies found an initial reduction of AD use during the peak of the first wave followed by an increased use in the subsequent periods [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies already investigated the impact of lockdown on antidepressant drug (AD) use. In particular, some studies reported an increased use of these medications during the first wave [15,16] that in some case persist also during the subsequent period of 2020 [17][18][19][20]. On the contrary, other studies found an initial reduction of AD use during the peak of the first wave followed by an increased use in the subsequent periods [21].…”
Section: Introductionmentioning
confidence: 99%